Dampak Program Kegiatan Desa Wisata Napal Jungur Terhadap Ekonomi Rumah Tangga Petani Studi Kasus Kecamatan Lubuk Sandi Kabupaten Seluma - Saputra, Zozi; Adriani, Evi; Fariadi, Herri (Jurnal Multidisiplin Dehasen (MUDE), 2025)
The development of the Napal Jungur tourist attraction has brought socioeconomic impacts to the farming community. The purpose of this research is to determine the social impact of the development of the Napal Jungur tourist attraction on the welfare of the community in Lubuk Sandi Sub-District, Seluma Regency, as well as to understand the economic impact on the development of the Napal Jungur tourist attraction in Seluma Regency. The focus of this research is on the development of the Napal Junggur tourist attraction on the Economic of Farmers' Households in Lubuk Sandi Sub-District, Seluma Regency. This research was conducted in the environment of the Napal Jungur tourist attraction in Lubuk Sandi Sub-District, Seluma Regency. The data collection techniques used in this research include observation, interviews, documentation, and a combination of all three (triangulation). In this study, the analysis method used is descriptive with a qualitative approach that includes analyses based on the research object that has been arranged beforehand to provide more focused results. Based on the research findings, the social impact of the development of the Napal Jungur tourist attraction includes increased social interaction with new people, competition among traders that requires them to interact with each other in running their businesses. The economic impact of the development of the Napal Jungur tourist attraction includes an increase in community income, thereby improving the welfare of the community.